The immunosuppressive effects of a novel recombinant LipQ (Rv2485c) protein of Mycobacterium tuberculosis on human macrophage cell lines. (June 2017) - Kumar, Anjani; Manisha,; Sangha, Gurkamaljit Kaur; Shrivastava, Anju; Kaur, Jagdeep
Abstract: Mycobacterium tuberculosis (MTB), an intracellular pathogen, still represents a major global health challenge. A number of mycobacterial macromolecules have been shown to target biological processes within host macrophages; however, the exact mechanism for the majority of these host pathogen interactions is still poorly understood. Moreover, the lipid metabolic pathway is one of the most important physiologic pathways that plays a vital role in the survival and infection of Mycobacterium tuberculosis . In present study, we investigated the effect of rLipQ from Mycobacterium tuberculosis H37Rv on macrophage functions in vitro .Our results demonstrate that rLipQ significantly lowers the expression level of pro-inflammatory cytokines (TNF-α& IFN-γ) and augments the level of anti inflammatory cytokines such as IL-4 & IL-10as compared to LPS stimulated macrophages. An up-regulation of anti-inflammatory and down-regulation of pro-inflammatory cytokines levels in rLipQ pretreated macrophages implies immuno-modulatory functions in TB patients. Interestingly, rLipQ also inhibited the expression of iNOS, TLR-2 and transcription factor NF-kB in LPS stimulated macrophages whereas the expression of TLR-4 remains unchanged. The inhibition in the expression of these signaling molecules has been correlated to the inhibition of NO production in macrophages. Taken together, these studies demonstrate that rLipQ is a novel lipase that is highly immunogenic and may play an important role in the virulence and pathogenesis of M. tuberculosis infection, by altering the balance of cytokines, which might help to assess prognosis and contribute to a better understanding against host–pathogen interactions. Highlights: M. tuberculosis Rv2485c (rLipQ) protein plays an important role in virulence. Purified recombinant LipQ protein inhibits LPS induced iNOS & NO production in human macrophages. rLipQ modulates human macrophage activation via NF-κB signalling. Provide a new cellular target modulate macrophage-mediated immunosuppression.